2023
DOI: 10.1186/s12866-023-02893-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacteriophages for combating multidrug-resistant Listeria monocytogenes from dairy cattle farms in conjugation with silver nanoparticles

Abstract: Background This study aims to achieve biocontrol of multidrug-resistant Listeria monocytogenes in dairy cattle farms which poses a severe threat to our socio-economic balance and healthcare systems. Methods Naturally occurring phages from dairy cattle environments were isolated and characterized, and the antimicrobial effect of isolated L. monocytogenes phages (LMPs) against multidrug-resistant L. monocytogenes strains were assessed alone and in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This effect included not only the dissipation of the biofilm but also lethality toward the biofilm-forming cells. Similarly, phages ZCSE2 and ZCSE6 (of Myoviridae and Siphoviridae family, respectively) exhibited a synergistic effect with AgNPs against free Salmonella enterica cultures 56 , 57 , as did the mixture of phage LMP3 (of Podoviridae family) and AgNPs against liquid cultures of Listeria monocytogenes 58 . Additionally, mixing of phage ZCEC5 with AgNPs improved the effectiveness against free E. coli O157:H7 59 .…”
Section: Discussionmentioning
confidence: 94%
“…This effect included not only the dissipation of the biofilm but also lethality toward the biofilm-forming cells. Similarly, phages ZCSE2 and ZCSE6 (of Myoviridae and Siphoviridae family, respectively) exhibited a synergistic effect with AgNPs against free Salmonella enterica cultures 56 , 57 , as did the mixture of phage LMP3 (of Podoviridae family) and AgNPs against liquid cultures of Listeria monocytogenes 58 . Additionally, mixing of phage ZCEC5 with AgNPs improved the effectiveness against free E. coli O157:H7 59 .…”
Section: Discussionmentioning
confidence: 94%
“…The former combination reduced the bacterial counts below the detection limits after 2 h, while the latter combination allowed the re-growth of Listeria cells [ 117 ]. In a recent article, Elsayed et al [ 118 ] isolated and characterized six different phages from dairy cattle environments and assessed their antimicrobial effect against 22 different multidrug-resistant L. monocytogenes strains alone and in conjugation with silver nanoparticles (AgNPs). The authors showed that the bacteriophages attached to silver nanoparticles were protected from the harsh environmental conditions, enhancing their effectiveness in reducing L. monocytogenes growth (without regrowth) and excluding the possibility of phage to induce bacterial resistance.…”
Section: Biocontrol Of L Monocytogenes In Milk And...mentioning
confidence: 99%
“…Still, in the absence of clinical trials, to pose the basis for developing bacteriophage therapy against multidrug-resistant strains of L. monocytogenes, six (LMP1-LMP6) new phages were recently isolated and characterized for the host range and stability at wide ranges of pH and temperature. This led to the selection of one phage (LMP3) being more suitable for killing multidrug-resistant L. monocytogenes [60]. The in vitro conjugation of this phage with silver nanoparticles further demonstrated enhanced anti-Listeria monocytogenes activity and more stability [60].…”
Section: Livestock 421 Ruminantsmentioning
confidence: 99%
“…This led to the selection of one phage (LMP3) being more suitable for killing multidrug-resistant L. monocytogenes [60]. The in vitro conjugation of this phage with silver nanoparticles further demonstrated enhanced anti-Listeria monocytogenes activity and more stability [60]. New technologies, such as nanotechnology, may therefore be used to develop carriers of bacteriophages that are able to inexpensively improve stability and help to combat multidrug-resistant L. monocytogenes.…”
Section: Livestock 421 Ruminantsmentioning
confidence: 99%